Determining the Impact of Diet and Nutrition on Periodontal Health and Disease - Gaetano Isola (Issues and Development in Health Research Vol. 4, 2021)
During the last decades, the importance of micronutrients has been extensively reviewed, and it was concluded that the prevention and treatment of periodontitis should include correct daily nutrition and a correct balance between antioxidants, probiotics, natural agents, vitamin D, and calcium. Recently, there has been growing interest in the literature on the impact of nutraceutical dietary aliments on oral and general health. Periodontal diseases, chewing disorders, and many destructive oral inflammatory diseases are usually caused by an imbalance between host defense and environmental factors like smoking, poor nutrition, and a high percentage of periodontopathogenic bacteria. For these reasons, it is important also to focus attention on plaque control and also on improving host resistance through smoking and stress reduction, and a healthy diet. Numerous clinical and experimental studies have highlighted the presence of a strong association between periodontitis and some systemic diseases, in particular, cardiovascular diseases, diabetes, lung diseases and complications of pregnancy. The objective of this chapter was to analyze the impact of diet, micro- and macronutrients on oral health and to provides a current and thoughtful perspective on the relationship of diet and natural agents on oral and periodontal diseases through a correct clinical approach with the last and most important evidence that may determine good oral conditions and high quality of life.